A mobile of mobile learning object design for concept comprehension using reciprocal teaching strategies and augmented realty - A.T, Dayang Noorasura; Salam, Sazilah (International Conference on Computer Science and Automation Engineering (CSAE 2011), 2011)
This paper describes an on-going research project, in which we implement Reciprocal Teaching strategy to help undergraduate engineering students on comprehending the concept of basic circuit instruments. We examined 55 students who enrolled for electronic instrumentation subject containaing models designed to teach concept of D'Arsonval principle, basic component of a meter, measuring circuit resistance and circuit component arragement. We did a premilinary analysis by carrying out a survey on students' understanding level about the subject and class obervation on their learning progress. We found that students have difficulties in comcept comprehension for the sibject particulatly in visualizing the circuit component. Therefore, we propose a mobile learning that usea Reciprocal Teaching strategy with augmented with augmented reality (MLAR) is provided as a learning aid tool that helps students to achieve the learning aoutcome for the subject.